1945
DOI: 10.1111/j.1469-185x.1945.tb00444.x
|View full text |Cite
|
Sign up to set email alerts
|

The Shoot Apex in Pteridophytes

Abstract: Summary (1) Some of the developments which have made for a fuller understanding of the shoot apex in pteridophytes are discussed, particular attention being paid to morphogenetic processes, (2) Of the several interpretations of growth and cellular arrangement at the apex which have been advanced, that of Naegeli, in which the importance of the apical cell is emphasized, appears to be most applicable to the livingpteridophytes; Sachs's geometrical‐mechanical views emphasize another aspect of organization at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1949
1949
1986
1986

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…These range from 9 to 21 and are in general agreement with the shape of cells in other undifferentiated tissues. For a statement of conditions in the apical meristem of the shoot in ferns the reader is referred to Wardlaw (1945). This author has also published an extensive series of papers on experimental and analytical studies of pteridophytes, many of which are cited in his books (1952«, 1952&) and in later papers by himself and his colleagues.…”
Section: Growthmentioning
confidence: 99%
“…These range from 9 to 21 and are in general agreement with the shape of cells in other undifferentiated tissues. For a statement of conditions in the apical meristem of the shoot in ferns the reader is referred to Wardlaw (1945). This author has also published an extensive series of papers on experimental and analytical studies of pteridophytes, many of which are cited in his books (1952«, 1952&) and in later papers by himself and his colleagues.…”
Section: Growthmentioning
confidence: 99%
“…RECENT WORKERS (Camp, 1943;Maheshwari, 1945;Bailey, 1949) have suggested that taxonomic relationships be based upon a study of the plant from all fields of plant science. In addition to possible taxonomic considerations, comparative morphology should provide more basic facts concerning the development of the shoot apex since, as Wardlaw (1945) points out, it is the "seat of all primary formative activities." As a means toward these ends, this study compares the structure and development of the shoot apex and its derivatives in a large group of related plants.…”
mentioning
confidence: 99%
“…Summaries of the literature concerned with the shoot apex up to the present time can be found in the comprehensive reviews by Foster (1939Foster ( , 1941Foster ( , 1949, Engard (1944), Sifton (1944), Wardlaw (1945), Reeve (1948), and Philipson (1947Philipson ( , 1949 .…”
mentioning
confidence: 99%
“…This continuous acropetal differentiation of the procambium has been noted by many authors since the work of Esau (1942Esau ( , 1943. Exceptions to this pattern of development should be noted, as indicated by the recent work of Ball (1949) , Wardlaw (1945), and the Snows (1931,1933) where the initial procambial development is described as basipetal. Probably either pattern is possible as Hegediis (1949) has demonstrated.…”
mentioning
confidence: 93%